Challenges of State Civil Apparatus Human Resources in Adapting to Digital-Based Services in West Nusa Tenggara - Nurmaya; Ali Azhari; Hafiz Maulana; Anindiya Rizkila Cahyani; Cahyadi Kurniawan (Civic Governance and Public Administration, 2025)
State Civil Apparatus, which is commonly abbreviated as ASN, is contained in Law Number 5 of 2014 concerning the State Civil Apparatus.The role of the state civil apparatus here is very important in providing services, especially since they must be able to adapt to the presence of digital-based services. ASN must be able to adapt to the times from manual services to digital services. This study aims to determine the challenges of ASN human resources in adapting to the presence of digital-based services in NTB. The method used is qualitative descriptive, the data used is secondary data and data collection techniques in this study through existing documents and literature. The data analysis technique in this study uses the SWOT analysis technique, which is with four steps, namely strength identification, weakness analysis, opportunity identification, and threat analysis. The problem faced by ASN is the challenge of adapting state civil servants to digital services which requires ASN to switch and adapt to technological developments where the transition from manual services to digital services is needed, even though these adjustments require process and time. It turns out that in the transition from manual to digital, most employees have understood the digital-based service process, so that in the process of transitioning to digital, civil servants have understood digital.